2007
DOI: 10.1080/08860220701391662
|View full text |Cite
|
Sign up to set email alerts
|

The Diabetic Foot in End Stage Renal Disease

Abstract: Diabetic foot lesions remain a major cause of morbidity in patients with renal failure, especially those on dialysis. Foot complications are encountered at a more than twofold frequency in diabetic patients with end-stage renal disease, and the rate of amputations is 6.5-10 times higher in comparison to the general diabetic population. The causal pathways of the diabetic foot in renal failure are multiple and inter-related. Three major pathologies-neuropathy, ischemia, and infection-are the main contributory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 96 publications
(253 reference statements)
2
24
0
Order By: Relevance
“…Conversely, patients with diabetic nephropathy may exhibit more pronounced DSPN, and may therefore be at increased risk of severe diabetic foot lesions [147]. This information is important for the organization of an overall strategy for detecting, monitoring, and treating chronic microvascular complications.…”
Section: Nephropathymentioning
confidence: 99%
“…Conversely, patients with diabetic nephropathy may exhibit more pronounced DSPN, and may therefore be at increased risk of severe diabetic foot lesions [147]. This information is important for the organization of an overall strategy for detecting, monitoring, and treating chronic microvascular complications.…”
Section: Nephropathymentioning
confidence: 99%
“…Our study showed frequency of nephropathy was 36.99% in patients undergoing diabetic foot amputation and it is comparable to 20 -30% of diabetic patients having nephropathy as shown by American diabetic care and Broumand B. 11,12 This indicated that worsening of kidney function would affect the treatment out come and prognosis of foot ulcers in patients with diabetic foot. It is very important to improve the kidney function in the treatment of patients with diabetic foot ulcers.…”
Section: Discussionmentioning
confidence: 54%
“…Rate of amputation is 6-10 times higher in patients with diabetic nephropathy as compare to general diabetic patients who do not have nephropathy. 12 There are many reports in literature on the risk factors for diabetic foot complications. However, little data is available on the risk factor especially nephropathy, for amputation in diabetic Foot.…”
Section: Introductionmentioning
confidence: 99%
“…Foot complications are more common in diabetic patients with ESRD,24 and in those undergoing dialysis 25. Diabetic patients are more likely to require amputation than non-diabetics on HD,26 are more likely to require more major amputation (below-knee or above-knee),27 and are more likely to die following amputation,28 percutaneous intervention29 or critical limb ischaemia 30.…”
Section: What Effect Does Diabetes Have On Mortality and Morbidity Inmentioning
confidence: 99%